Isolation and characterization of sterols and an aliphatic alcohol from Tsuga dumosa D. Don of Nepal - Dhakal, Ramesh C; Kalauni, Surya K; Awale, Suresh; Shrestha, Kanti; Gewali, Mohan B (Scientific World, 2011)
In the course of our continuing research on Himalayan conifers, the phytochemical screening and isolation of chemical constituents of Tsuga dumosa D. Don of Nepali origin was carried out. Three sterols, namely â-sitosterol (1), stigmasterol (2), â-sitosterol glucoside (3) and an alcohol, nonacosan-10-ol (4) were isolated. Their structures were elucidated on the basis of spectroscopic evidences. Key Words: Phytochemical screening; Tsuga dumosa; Sterols; Nonacosan-10-ol. DOI: http://dx.doi.org/10.3126/sw.v9i9.5511 SW 2011; 9(9): 16-17